PENGARUH MODEL PEMBELAJARAN MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND, REVIEW (MURDER) TERHADAP HASIL BELAJAR KONTRUKSI JALAN DAN JEMBATAN SISWA KELAS XI PROGRAM KEAHLIAN DESAIN PERMODELAN DAN INFORMASI BANGUNAN SMK NEGERI 5 MEDAN - Lamhot Siagian; Sutrisno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of the Mood, Understand, Recall, Digest, Expand, Review (MURDER) learning model on students’ learning outcomes in Road and Bridge Construction among eleventh-grade students of the Building Design and Information Modeling (DPIB) Program at SMK Negeri 5 Medan in the 2025/2026 academic year. This study was motivated by the relatively low student learning outcomes, indicated by the number of students who had not yet achieved the Minimum Learning Competency Criteria, as well as the learning process that was still dominated by the Direct Instruction model, resulting in limited student participation during classroom activities. This study employed a quasi-experimental research method using a Nonequivalent Control Group Design. The population consisted of 90 eleventh-grade DPIB students at SMK Negeri 5 Medan divided into three classes. The samples were selected using a cluster random sampling technique, resulting in two classes: an experimental class that received the MURDER learning model and a control class that received the Direct Instruction learning model. Data collection was conducted using a multiple-choice learning achievement test. The data were analyzed through normality tests, homogeneity tests, and hypothesis testing. The findings revealed a significant difference in learning outcomes between students taught using the MURDER learning model and those taught using the Direct Instruction model. This was evidenced by the hypothesis testing result, where the calculated t-value (3.07) was greater than the t-table value (2.00), indicating that H₀ was rejected and H₁ was accepted. The average learning outcome score of the experimental class was 82.46, while the control class achieved an average score of 74.86. Based on the Minimum Mastery Criterion (MMC) of 75, the experimental class successfully achieved classical learning mastery. Based on the findings, it can be concluded that the MURDER learning model is more effective than the Direct Instruction model in improving students’ learning outcomes in Road and Bridge Construction, particularly in the Implementation, Supervision, and Maintenance of Road Construction (P3K Jalan) element among eleventh-grade DPIB students at SMK Negeri 5 Medan in the 2025/2026 academic year.